Efisiensi Pelayanan Kesehatan Dasar di Kabupaten Pemalang Menggunakan Data Envelopment Analysis - Wahyudi Wahyudi; Lutfan Lazuardi; Mubasysyir Hasanbasri (Center for Health Policy and Management, 2015)
Background. Limited availability of health resources has in- fluenced the health care performance at the health centers. In addition, the health office and health centers are required to be able to manage the available resources to provide optimally healthcare by putting priority on the efficiency in every opera- tional of health centers. The objective of the study is to ana- lyze relative efficiency of primary health care, to find out the efforts for efficiency increase on the inefficient health cen- ters, and to estimate the influence of environmental/ contex- tual factors on the efficiency of primary health care in the health centers.Methods. A descriptive quantitative study was conducted using two-stage data envelopment analysis (DEA). The first stage was to measure efficiency of primary health care, and the second stage was to determine the influence of environ- mental/ contextual factors on the efficiency of primary health care. This study using secondary data of the outpatient per- formance reports in 2013 on 22 health centers in Pemalang regency. Results: Efficiency measurement using DEA-VRS model with output orientation obtained 50% of health centers technically efficient and 50% of health centers technically inefficient. From the efforts of increasing efficiency on the inefficient Health Centers obtained targets of reducing input of workforce re- sources as much as 49 personnels and targets of increasing output of primary health care as much as 154.911 outpatient visits. In the tobit regression analysis showed the population was statistically significant with positive sign, while the popu- lation density, the proportion of visits the poor society and the other primary health facilities are not significant with positive sign. Conclusion. Inefficiencies of health centers was caused by the excessive number of health workforce and low utilization of primary health care by the society. DEA method can be used as a tool to measure the level of efficiency of primary health care in health centers , to provide information on the cause of inefficiency, and to determine the target of efficiency increas- ing on the inefficient health centers. Latar Belakang: Ketersediaan sumber daya kesehatan yang terbatas mempengaruhi kinerja pelayanan puskesmas. Di sisi lain dinas kesehatan dan puskesmas dituntut mampu mengelola sumber daya kesehatan yang tersedia untuk menyelenggara- kan pelayanan kesehatan secara optimal dengan mengedepan- kan efisiensi dalam setiap operasional puskesmas. Tujuan penelitian ini adalah untuk menganalisis tingkat efisiensi relatif pelayanan kesehatan dasar puskesmas, mengetahui upaya peningkatan efisiensi bagi puskesmas inefisien dan memperkira- kan pengaruh faktor-faktor lingkungan/ kontekstual terhadap efisiensi pelayanan kesehatan dasar puskesmas. Metode: Jenis penelitian deskriptif kuantitatif menggunakan metode data envelopment analysis (DEA) dua tahap. Tahap pertama untuk mengukur efisiensi pelayanan kesehatan dasar. Tahap kedua untuk mengetahui pengaruh faktor-faktor lingku- ngan/ kontekstual terhadap efisiensi pelayanan kesehatan dasar. Penelitian ini menggunakan data sekunder laporan kinerja pelayanan rawat jalan 22 puskesmas di Kabupaten Pemalang tahun 2013. Hasil: Pengukuran efisiensi menggunakan model DEA VRS orientasi output diperoleh 50% puskesmas efisien teknis dan 50% puskesmas inefisien teknis. Dari upaya peningkataan efi- siensi pada puskesmas inefisien diperoleh target pengurangan input sumber daya ketenagaan puskesmas ssebanyak 49 personil dan target peningkatan output pelayanan kesehatan dasar sebanyak 154.911 kunjungan rawat jalan. Hasil analisis regresi tobit menunjukkan populasi penduduk signifikan dengan arah hubungan positif terhadap efisiensi teknis pelayanan kese- hatan dasar puskesmas. Sedangkan kepadatan penduduk, pro- porsi kunjungan masyarakat miskin dan sarana kesehatan dasar lain tidak signifikan dengan arah hubungan positif. Kesimpulan: Ketidakefisienan puskesmas disebabkan oleh penggunaan sumber daya ketenagaan puskesmas yang berle- bih dan rendahnya pemanfaatan pelayanan kesehatan dasar oleh masyarakat. Metode DEA dapat digunakan sebagai alat untuk mengukur tingkat efisiensi pelayanan kesehatan dasar puskesmas, memberikan informasi penyebab puskesmas inefisien dan menentukan target peningkatan efisiensi pada puskesmas inefisien.